2021
DOI: 10.3390/s21155052
|View full text |Cite
|
Sign up to set email alerts
|

User Experience in Social Robots

Abstract: Social robots are increasingly penetrating our daily lives. They are used in various domains, such as healthcare, education, business, industry, and culture. However, introducing this technology for use in conventional environments is not trivial. For users to accept social robots, a positive user experience is vital, and it should be considered as a critical part of the robots’ development process. This may potentially lead to excessive use of social robots and strengthen their diffusion in society. The goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…According to previous literature review studies, researchers prefer questionnaire-based designs (around 80% of the literature reviewed and interviews). Hardly any studies were found on real-time, real user experience of the process [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous literature review studies, researchers prefer questionnaire-based designs (around 80% of the literature reviewed and interviews). Hardly any studies were found on real-time, real user experience of the process [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to find similar solutions in intelligent tutoring systems (ITSs), but the explicit agentic nature of robots often brings additional options and problems (32). It has been observed that students learn more efficiently when they are given the right emotional support approach, help with meta-cognitive learning techniques, know when to take a break, and encourage correct assistance-seeking behaviour, among other things (33). Combined with appropriate gestures, acceptable and congruent gaze behaviour, expressive and attention-guiding behaviours, and timely nonverbal behaviours, these actions boost students' retention and learning (34).…”
Section: Technological Hurdles While Developing Robot Instructorsmentioning
confidence: 99%
“…When dealing with these issues, three contributions are made to the literature. First, although previous studies have assessed the HRI experience (a review is proposed by Shourmasti et al [ 22 ]), our research is among the first to make the assessment using a structural model after experiencing interactions with a real social robot in a front-office service environment. Although there are some precedents in hospitality, such as Tung and Au [ 23 ], who studied the reviews published by customers on TripAdvisor, Booking.com, etc., where they rated their experience of staying in hotels serviced by robots, to the best of our knowledge there are no studies of direct experiences that analyse the five customer personalities.…”
Section: Introductionmentioning
confidence: 99%